Ultrasound-Guided Supraclavicular Block as a Primary Anesthetic for Humerus Biopsy in a High-Risk Patient with a Compressive Goiter and Atrial Fibrillation: A Case Report - Muhammad Husni Thamrin; Muhammad Ridho Aditya; Nabila Vika Intansari (Open Access Indonesian Journal of Medical Reviews, 2025)
The anesthetic management of patients with multiple severe comorbidities presents a formidable clinical challenge. Pathological fractures secondary to metastatic disease often require procedural intervention in individuals with pre-existing cardiopulmonary, airway, and cerebrovascular compromise. General anesthesia in such patients carries a prohibitively high risk of hemodynamic collapse, airway loss, and perioperative mortality. We present a case where a targeted regional anesthetic technique was pivotal in ensuring patient safety. A 59-year-old woman with a pathological fracture of the right humerus, suspected to be a metastasis from thyroid carcinoma, was scheduled for a core needle biopsy. Her medical history was profoundly complex, including a massive, airway-compressing thyroid goiter, persistent atrial fibrillation, recent ischemic stroke with residual hemiparesis, bilateral pneumonia with pulmonary edema, uncontrolled type 2 diabetes mellitus, and acute-on-chronic kidney disease. Given the extreme risks associated with general anesthesia and airway manipulation, we opted for an ultrasound-guided right supraclavicular brachial plexus block as the sole anesthetic. The block was performed successfully using 20 mL of 1.5% lidocaine with epinephrine, providing dense sensorimotor anesthesia of the upper limb. The patient remained hemodynamically stable, spontaneously breathing, and comfortable throughout the procedure, with no perioperative complications. In conclusion, this case demonstrates that an ultrasound-guided supraclavicular block is a safe, effective, and hemodynamically superior alternative to general anesthesia for upper limb procedures in a patient with a confluence of critical airway, cardiac, pulmonary, and neurological comorbidities. This approach obviates the need for airway instrumentation, preserves spontaneous ventilation, and minimizes systemic physiological trespass, thereby enhancing patient safety in the highest-risk surgical populations.